Stone cold - Baldacci, David (New York : Grand Central Pub., 2007)
"Oliver Stone and the Camel Club are back in their most dangerous adventure yet, a war on two fronts"--Provided by the publisher.
Keywords: Stone, Oliver (Fictitious character) -- Fiction; Camel Club (Imaginary organization) -- Fiction; Secret societies -- Fiction; Swindlers and swindling -- Fiction; Casinos -- Fiction; Intelligence service -- Fiction; Murder -- Fiction; Washington (D.C.) -- Fiction; Political fiction; Suspense fiction